(Invited) Epitaxial Lift-Off of GaN and Related Materials for Device Applications. (3rd July 2019) - Fay, Patrick; Wang, Jingshan; Cao, Lina; Xie, J; Beam, Edward; McCarthy, Robert; Reddy, Rekha; Youtsey, Chris
Abstract : The use of epitaxial lift-off with GaN and other III-N based materials offers substantial benefits for devices across a wide range of applications. Examples include devices for power control and conversion, microwave and millimeter-wave transmitters and receivers, sensors, LEDs and detectors, and many others. For these applications, epitaxial lift-off provides a key additional degree of freedom in fabrication processing and integration, offering potential benefits to the electrical, thermal, and optical properties of devices, as well as enhancing the ability of these devices to be heterogeneously integrated with other materials at low cost. We provide here an overview of this technology and its benefits.